Coinage metal complexes with bridging hybrid phosphine–NHC ligands: synthesis of di- and tetra-nuclear complexes12. Issue 12 (17th February 2016) - Simler, Thomas; Braunstein, Pierre; Danopoulos, Andreas A.
Abstract : P–NHC-type hybrid ligands were accessed through a modular synthesis and afforded di- and tetra-nuclear coinage metal complexes with functional bridging ligands. Abstract : A series of P–NHC-type hybrid ligands containing both PR2 and N-heterocyclic carbene (NHC) donors on meta -bis-substituted phenylene backbones, L Cy, L t Bu andL Ph (R = Cy, t Bu, Ph, respectively), was accessed through a modular synthesis from a common precursor, and their coordination chemistry with coinage metals was explored and compared. Metallation ofL Ph · n (HBr) ( n = 1, 2) with Ag2 O gave the pseudo-cubane [Ag4 Br4 (L Ph )2 ], isostructural to [Ag4 Br4 (L R )2 ] (R = Cy, t Bu) (T. Simler, P. Braunstein and A. A. Danopoulos, Angew. Chem., Int. Ed., 2015, 54, 13691), whereas metallation ofL R ·HBF4 (R = Ph, t Bu) led to the dinuclear complexes [Ag2 (L R )2 ](BF4 )2 which, in the solid state, feature heteroleptic Ag centres and a 'head-to-tail' (HT) arrangement of the bridging ligands. In solution, interconversion with the homoleptic 'head-to-head' (HH) isomers is facilitated by ligand fluxionality. 'Head-to-tail' [Cu2 Br2 (L R )2 ] (R = Cy, t Bu) dinuclear complexes were obtained fromL R ·HBr and [Cu5 (Mes)5 ], Mes = 2, 4, 6-trimethylphenyl, which also feature bridging ligands and heteroleptic Cu centres. Although the various ligandsL R led to structurally analogous complexes for R = Cy, t Bu and Ph, the rates of dynamic processes occurring in solution are dependent on R, with faster rates for R = Ph. Transmetallation of both NHC and P donor groups from [Ag4 Br4 (L t Bu )2 ] to Au I by reaction with [AuCl(THT)] (THT = tetrahydrothiophene) led toL t Bu transfer and to the dinuclear complex [Au2 Cl2 L t Bu ] with oneL t Bu ligand bridging the two Au centres. Except for the silver pseudo-cubanes, all other complexes do not exhibit metallophilic interactions.